2017
DOI: 10.4025/cienccuidsaude.v16i1.34532
|View full text |Cite
|
Sign up to set email alerts
|

<b>Significado da violência física ocupacional para o trabalhador de enfermagem na dinâmica familiar e social/ The meaning of physical violence at the workplace for nursing workers within family and social dynamics<b>

Abstract: 1O presente estudo não foi discutido em eventos científicos ou publicado em revistas estrangeiras. Extraído da dissertação de mestrado intitulada: Percepção dos trabalhadores de enfermagem em relação à violência física ocupacional em serviços de urgência e emergência hospitalares apresentada ao Programa de Pós-Graduação em Enfermagem da Universidade Estadual de Londrina (UEL Dayane Aparecida Scaramal* Maria do Carmo Fernandez Lourenço Haddad** Mara Lúcia Garanhani*** Maria José Quina Galdino**** Paloma de Souz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
(11 reference statements)
1
1
0
5
Order By: Relevance
“…16 A research performed with nursing professionals who were victims of aggression, in an urgency and emergency sector, in the Paraná State, found that workers do not feel prepared to face and manage situations of violence in the workplace, which do not have the necessary skills to identify situations of risk and that there is a weakness in job security and institutional support. 17 In Latin America, 4,[17][18][19][20] violence is felt and perceived by health workers, especially in areas with drug trading and armed men, who terrify professionals and make it difficult to provide care to the population that works and resides in these territories, then corroborating the findings of the present study.…”
Section: Discussionsupporting
confidence: 86%
“…16 A research performed with nursing professionals who were victims of aggression, in an urgency and emergency sector, in the Paraná State, found that workers do not feel prepared to face and manage situations of violence in the workplace, which do not have the necessary skills to identify situations of risk and that there is a weakness in job security and institutional support. 17 In Latin America, 4,[17][18][19][20] violence is felt and perceived by health workers, especially in areas with drug trading and armed men, who terrify professionals and make it difficult to provide care to the population that works and resides in these territories, then corroborating the findings of the present study.…”
Section: Discussionsupporting
confidence: 86%
“…Algunos factores explican porque hay una mayor incidencia de violencia en el área de enfermería, como el contacto directo y frecuente con los pacientes (31) , la angustia o el sufrimiento de los agresores (32) , el contexto estresante (32) , las condiciones precarias de trabajo y el desarrollo de la profesión en el contexto histórico-social (33) . El hecho de que los enfermeros brinden asistencia directa a los usuarios en los diferentes servicios de salud e interactúen con otros miembros del equipo favorece el acceso a estos trabajadores en momentos de quejas y conflictos (15) , convirtiéndolos en un blanco fácil para conductas abusivas.…”
Section: Discussionunclassified
“…Some factors explain the higher occurrence of violence in Nursing, such as direct and frequent contact with patients ( 31 ) , the aggressors’ anguish or suffering ( 32 ) , the stressful context ( 32 ) , precarious working conditions and the very development of the profession in the historical-social context ( 33 ) . Providing direct assistance to users in different health services and interacting with other team members favor access to these workers in times of complaints and conflicts ( 15 ) , turning them into easy targets for abusive behaviors.…”
Section: Discussionmentioning
confidence: 99%